Ambiguous entanglements: infrastructure, memory and identity in indigenous Evenki communities along the Baikal–Amur Mainline - Olga Povoroznyuk (Department of Social and Cultural Anthropology, Faculty of Social Sciences, University of Vienna) (Social Anthropology, 2021)
The abstract is available here: https://uscholar.univie.ac.at/o:1535963 The abstract is available here: https://uscholar.univie.ac.at/o:1535963